Peter Weiss: Experiment und Engagement heute (Studia theodisca, 2024)
In the introductory essay, the volume’s editors trace the project that gave rise to this collection of contributions on Peter Weiss, his work, and his fortunes back to the events celebrating the centenary of his birth in 2016. The reflections start from Milo Rau, as an example of a contemporary author and director who finds in the mastery of Peter Weiss a point of reference for an art combining formal experimentalism with political engagement. The relevance of this present-day reference to Weiss as an example of the “aesthetics of resistance” is then addressed in detail, which leads on to the discussion of the main idea and thematic structure of the volume.The twelve papers are divided into two equal halves. In the first section, entitled “Essay und Prosa – Experimente mit Subjekt, Kunst und Politik”, six scholars investigate Peter Weiss’s essayistic and fictional writing, its cultural and artistic context, and its legacy for literature up to the 21st century. Lesser-known articles in Swedish and seminal interventions in the public debates of the 1960s, experimental prose and canonical novels, are thus reinterpreted using the tools of contemporary literary theory.In the second section, a further six scholars examine Weiss’s cinematographic and theatrical work and his reflections on media and performance. These contributions give new insights into Weiss’s documentary films, revolutionary dramas, and media aesthetics and politics, as well as their influence up to the present day. Under the title “Performative Engagements: Film, Theater, Medien”, contributions are brought together that range from earlier models, such as Hölderlin, Artaud, and Brecht, to contemporaries like Pier Paolo Pasolini, and finally to today’s theatre, again with Milo Rau.